« Dans les forêts d’Adjarie… » : Franchir la frontière turco-soviétique, 1922-1937 - Étienne Forestier-Peyrat (Diasporas: Circulations, Migrations, Histoire)
This paper studies human migrations at the border between the Soviet Union and Turkey in the 1920s-1930s. It focuses on the case of Adjara, an autonomous republic of Soviet Georgia, which constitutes a key hub for these migrations in the interwar period. Building upon archives left by Soviet border guards, the paper analyses the different scales involved in the process and the transformations of the border regime which can be observed starting from the late 1920s.